1963
DOI: 10.1099/00221287-31-3-375
|View full text |Cite
|
Sign up to set email alerts
|

The Fixation of Tetanus Toxin, Strychnine, Serotonin and other Substances by Ganglioside

Abstract: SUMMARYAlthough tetanus toxin is fixed by brain ganglioside, it is not fixed by a number of substances more or less closely related to brain ganglioside, or by naturally occurring brain ganglioside not containing hexosamine, or by a hexosamine-containing ganglioside from Tay-Sachs brain. Isolated brain gangliosides may vary considerably in their toxin-fixing capacities.In chloroform + methanol extracts of brain a number of gangliosides which differ in ability to fix toxin can be separated chromatographically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1968
1968
1987
1987

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…As described above, we have observed similar low levels of toxin-induced channel activity in asolectin membranes at a symmetric pH of 7.0. This activity was not affected by the presence of ganglioside GTlb (asolectin to ganglioside ratio 9:1), a putative receptor for tetanus toxin (23).…”
Section: Methodsmentioning
confidence: 95%
“…As described above, we have observed similar low levels of toxin-induced channel activity in asolectin membranes at a symmetric pH of 7.0. This activity was not affected by the presence of ganglioside GTlb (asolectin to ganglioside ratio 9:1), a putative receptor for tetanus toxin (23).…”
Section: Methodsmentioning
confidence: 95%
“…Cells were grown on 0.1% gelatin-coated glass (for PCC7 cells) or tissue culture plastic coverslips (for C1003 cells). Stage-specific mouse embryonic antigen (SSEA-1) (24) and tetanus toxin binding sites (25) were revealed on cells fixed with 3% paraformaldehyde (10 min at room temperature). Mouse monoclonal anti-SSEA-1 antibody was generously provided by D. Solter (24).…”
Section: Methodsmentioning
confidence: 99%
“…The precise nature of the 5-HT receptor has been a subject of interest for several years. Woolley and Gommni (51) (52) demonstrated that gangliosides in aqueous media could bind 5-HT as well as other pharmacologic agents such as lysergic acid diethylamide and chlorpromazine. Gielen Human Platelet Gangliosides (53,54) (35) reported that 74% of the total sialic acid of frozen and thawed platelets was liberated by neuraminidase.…”
Section: Discussionmentioning
confidence: 99%